USING ROLE PLAY TECHNIQUES IN IMPROVING ENGLISH SPEAKING COMPETENCY ON THE PERSONALITY TYPES - Asriyani, Retny; Suryawati, Dewa Ayu; Anggayana, I Wayan Agus (International Conference on Cultural Studies, 2019)
This study discusses Personality Type on speaking competence. Specifically, this study aims to investigate whether any of the students helped him use the role of play and the conventional techniques he possessed (a) significant difference of speaking competency between students who are taught by using role play technique and who are taught by conventional technique, (b) significant difference of speaking competency between extrovert students and introvert students, (c) the interactional effect of the implementation of teaching techniques and students’ personality types in speaking competency, (d) significant difference of speaking competency between extrovert students who are taught by using role play technique and those who are taught by using conventional technique and (e) significant difference of speaking competency between introvert students who are taught by using role play technique and those who are taught by using conventional technique. This research will be conducted on Akademi Komunitas Manajemen Perhotelan Indonesia. State that Post-test only control group design considers two groups where one of them receives experimental assistance, while the other does not. In the end, the two groups were given a post-test. After approval, students are given care. The experimental group entitled Role of Playing Techniques and control groups won with conventional techniques in the form of Chain Drill. The treatment lasts for 8 meetings. At the end of the second class a speaking competency test was given. After that, the data will be combined and analyzed inferentially. Inferential analysis is done to test the research hypothesis and to answer the research questions for this study.